Array-Structured Double-Ion Cooperative Adsorption Sites as Multifunctional Sulfur Hosts for Lithium–Sulfur Batteries with Low Electrolyte/Sulfur Ratio - Guo, Junling; Huang, Yuanyuan; Zhao, Siyuan; Li, Zixuan; Wang, Zhuo; Shao, Guosheng; Liu, Jinping (ACS nano, 2021)
Low electrolyte/sulfur ratio (E/S) is a crucial factor that promotes the development of lithium–sulfur batteries (LSBs) with desired energy density. However, it causes multiple problems, including a strong “shuttle effect” during both the cycle and storage process, and limited sulfur utilization. Herein, we develop a Na2Ti6O13 (NTO) nanowire array as a multifunctional sulfur host to simultaneously tackle both the above problems. The synergistic coordination between Na and Ti cations in NTO can accelerate the conversion of soluble polysulfides (PSs) to insoluble sulfides and significantly enhance their adsorption. Therefore, accumulation of PSs, which is the primary cause of the “shuttle effect”, can be avoided in two ways. One is fast conversion kinetics during cycles; another is strong PS adsorption, which can suppress the disproportionation of PSs during storage. The as-prepared array represents an easy-to-infiltrate structure with efficient electron transport that allows good wetting ability of the conductive surface toward the electrolyte. Therefore, it helps improve sulfur utilization that is mainly limited by the presence of unwetted conductive surface. Consequently, NTO/sulfur array cathodes exhibit high sulfur utilization and extended cycle- and shelf-lives at a low E/S (5:1). Our work suggests that array materials featuring cooperative multi-ion adsorption sites are promising hosts for LSBs.